2013
DOI: 10.3109/17435390.2013.832430
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle-specific mitotoxicity inDaphnia magna

Abstract: Silver nanoparticles (Ag NPs) are gaining popularity as bactericidal agents in commercial products; however, the mechanisms of toxicity (MOT) of Ag NPs to other organisms are not fully understood. It is the goal of this research to determine differences in MOT induced by ionic Ag(+) and Ag NPs in Daphnia magna, by incorporating a battery of traditional and novel methods. Daphnia embryos were exposed to sublethal concentrations of AgNO3 and Ag NPs (130-650 ng/L), with uptake of the latter confirmed by confocal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 56 publications
4
25
0
Order By: Relevance
“…These changes could be attributed to increased mitochondrial damage by AgNPs. Sublethal treatment with Ag + did not show an identical response which is consistent with Stensberg et al (2014) who observed different mechanisms of toxicity for Ag + and AgNPs in D. magna. As Ag + may dissolve from AgNPs, these two types of Ag act complimentary and could produce a greater toxic response together.…”
Section: Oxidative Stress Responsesupporting
confidence: 92%
See 2 more Smart Citations
“…These changes could be attributed to increased mitochondrial damage by AgNPs. Sublethal treatment with Ag + did not show an identical response which is consistent with Stensberg et al (2014) who observed different mechanisms of toxicity for Ag + and AgNPs in D. magna. As Ag + may dissolve from AgNPs, these two types of Ag act complimentary and could produce a greater toxic response together.…”
Section: Oxidative Stress Responsesupporting
confidence: 92%
“…Several studies reported that AgNPs induced toxicity, uptake, and accumulation in D. magna (Bondarenko et al 2013;Gaiser et al 2011;Stensberg et al 2014;Asghari et al 2012;Hoheisel et al 2012;Zou et al 2014). In this study, the immobilization and subsequent mortality of D. magna was dependent on exposure concentrations and time.…”
Section: Agnp Acute Toxicity To D Magnamentioning
confidence: 66%
See 1 more Smart Citation
“…In contrast, toxicities of NPs of other metals compared in the same study (CuO, ZnO) were primarily caused by the dissolved fractions exclusively (Seo et al 2014). Correspondingly, (Stensberg et al 2014) revealed that silver nanoparticles had greater impacts on mitochondrial functions in D. magna (in comparison with the effects of dissolved Ag + ), which could mechanistically explain the observed higher toxicities of Ag nanoparticles.…”
Section: Resultsmentioning
confidence: 61%
“…Truncated triangular silver nanoplates with a lattice plane as the basal plane displayed stronger biocidal action to gram-negative bacterium Escherichia coli than Ag + (Pal et al, 2007). Sublethal concentrations of Ag + and AgNPs exposure to Daphnia embryos also revealed that there is an AgNP-specific mitotoxicity to Daphnia magna (Stensberg et al, 2014). AgNP-exposed common grass, Lolium multiflorum, failed to develop root hairs, had highly vacuolated and collapsed cortical cells, which was not observed for Ag + -exposed group (Yin et al, 2011).…”
Section: Introductionmentioning
confidence: 91%